Physical Activity Improves Muscle Strength and Reduces Inflammatory Markers in Diabetic Elderly Patients - Fitriyah, Lailatul; Sunarti, Sri (Fakultas Kedokteran Universitas Brawijaya, 2014)
Regular exercise has an effect on muscle strength and inflammatory markers. The aim of this study is to determine the relation of regular exercise with muscle strength and inflammatory markers (IL-6, CRP) in diabetic elderly compared to non-diabetic ones. A case control study was conducted to 30 elderly by giving them regular exercise. Fifteen subjects were diabetic and the other fifteen were non-diabetic. The data were analyzed using Chi-Square, independent t-Test and Mann Whitney. The result shows handgrip 24,9(14,8-34,6)kg in diabetic vs. 25(6,8-42,1)kg in non-diabetic (p=0,673); 4 meters walk was 3,38(2,34-8,18)s in diabetic vs 3,26(2,06-4,36)s in non-diabetic (p=0,263); IL-6 level was 1,61(0,37-14,02)pg/mL in diabetic vs 1,47(0,52-10,17)pg/mL in non-diabetic (p=0,983); CRP level was 0,23(0,18-0,33)mg/dL in diabetic vs 0,22(0,11-1,01)mg/dL in non-diabetic (p=0,622). HbA1C was 7,35 (5,9-13)%. There is no significant difference in muscle strength and inflammatory markers on the diabetic and non-diabetic groups who exercise regularly. This study shows that regular exercise and well-controlled HbA1C give a good impact on muscle strength and inflammatory markers of the diabetic elderly patients.Keywords: CRP, diabetes, IL-6, elderly, exercise